Management of Madrasah Head in Implementing Character Education in MIN 2 Batang Hari - Amirudin Amirudin; Maryam Maryam; Zilawati Zilawati; Derr Xin (P3M IAI Nusantara Batang Hari, 2022)
This study aimed to find out about how the management of the madrasah principal in implementing character education in MIN Sengati Gedang, Mersam District. The importance of this study because the principal and all madrasah citizens are responsible for improving the quality of education in Indonesia. Therefore, it becomes a demand to be able to make important contributions in the field of education to produce good quality, competitive, professional, innovative students in possessing good character for the nation's future generations.